Store-operated Ca2+ entry (SOCE) regulates melanoma proliferation and cell migration. - Masanari Umemura; Erdene Baljinnyam; Stefan Feske; Mariana S De Lorenzo; Lai-Hua Xie; Xianfeng Feng; Kayoko Oda; Ayako Makino; Takayuki Fujita; Utako Yokoyama; Mizuka Iwatsubo; Suzie Chen; et al. (PLoS ONE)
Store-operated Ca(2+) entry (SOCE) is a major mechanism of Ca(2) (+) import from extracellular to intracellular space, involving detection of Ca(2+) store depletion in endoplasmic reticulum (ER) by stromal interaction molecule (STIM) proteins, which then translocate to plasma membrane and activate Orai Ca(2+) channels there. We found that STIM1 and Orai1 isoforms were abundantly expressed in human melanoma tissues and multiple melanoma/melanocyte cell lines. We confirmed that these cell lines exhibited SOCE, which was inhibited by knockdown of STIM1 or Orai1, or by a pharmacological SOCE inhibitor. Inhibition of SOCE suppressed melanoma cell proliferation and migration/metastasis. Induction of SOCE was associated with activation of extracellular-signal-regulated kinase (ERK), and was inhibited by inhibitors of calmodulin kinase II (CaMKII) or Raf-1, suggesting that SOCE-mediated cellular functions are controlled via the CaMKII/Raf-1/ERK signaling pathway. Our findings indicate that SOCE contributes to melanoma progression, and therefore may be a new potential target for treatment of melanoma, irrespective of whether or not Braf mutation is present.